EVALUASI KINERJA RANTAI PASOK SAYURAN ORGANIK DENGAN PENDEKATAN SUPPLY CHAIN OPERATION REFERENCE (SCOR) - Dwi Apriyani; Rita Nurmalina; Burhanuddin Burhanuddin (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. The purpose of this study is to analyze the performance of organic vegetable supply chains in each member chain to determine the direction of improvement in the fulfillment of consumer needs optimally. The performance of supply chains at the farm level will be differentiated by individuals and commodities. The analytical method used is the Supply Chain Operational Reference (SCOR) model taking into account the internal and external attributes. The primary data used is taken through observation and interview process, meanwhile secondary data obtained from related institutions. The results of measuring the performance of organic vegetable supply chains at all levels of the responsiveness and flexibility attributes have achieved the superior performance position. Meanwhile, the value of organic vegetable supply chain performance on asset attributes at the farm level only reaches a good position. But at the corporate level has reached the best performance position (superior). In general, the performance of the organic vegetable supply chain on the cost attribute still has not achieved good performance. So there is the need for improvement efforts through minimization of cost in each supply chain activity to improve performance.